Large-scale multiple language translation accelerator at the United Nations - Pouliquen, Bruno; Elizalde, Cecilia; Junczys-Dowmunt, Marcin; Mazenc, Christophe; García-Verdugo, José (Proceedings of the 14th Machine Translation Summit, 2013)
Described is a large#scale implementation of a Moses#based machine translation system in the United Nations aiming at accelerating the work of translators. The system (called TAPTA4UN) has been trained on extensive parallel corpora in 6 languages. Both automatic and human evaluations are provided. The system is now used in production by professional translators. The technical challenges of scalability and the final evaluation by users are also described.